Rare earth composite magnetic material, rare earth composite magnetic wave-absorbing material and preparation method of rare earth composite magnetic wave-absorbing material

The rare earth permanent magnet alloy particles were prepared by ball milling and composited with magnetic metal fine powder, and a multi-layer matching structure design was adopted to solve the problem of limited absorption performance of ferromagnetic metal fine powder in the high frequency range, and achieve wide frequency absorption characteristics and efficient wave absorption performance.

CN119581161AActive Publication Date: 2025-03-07BEIJING INST OF ENVIRONMENTAL FEATURES

Patent Information

Application Number
CN202411711729.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-07
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The microwave absorption performance of existing ferromagnetic metal powders in the high frequency range is limited by the Snoek limit and high dielectric constant, resulting in poor impedance matching and unable to fully exert magnetic loss characteristics.

Method used

Rare earth permanent magnet alloy particles are prepared by ball milling method and are compounded with magnetic metal micropowder, their electromagnetic parameters are optimized, heterogeneous interfaces are formed, dielectric constant is regulated to optimize impedance matching, and rare earth composite magnetic wave absorbing materials are prepared by designing multi-layer matching structures.

Benefits of technology

It significantly improves the wave absorption performance of rare earth composite magnetic materials, realizes wide-frequency absorption characteristics, and has an effective absorption bandwidth of more than 2.12GHz, optimizing impedance matching and magnetic loss characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581161A_ABST
    Figure CN119581161A_ABST
Patent Text Reader

Abstract

The invention relates to a rare earth composite magnetic material, a rare earth composite magnetic wave-absorbing material and a preparation method thereof. The rare earth composite magnetic material comprises rare earth permanent magnet alloy particles and magnetic metal micro powder which are compounded together, and the surfaces of the rare earth permanent magnet alloy particles are modified with oleic acid. The rare earth composite magnetic wave-absorbing material is obtained by arranging rare earth composite magnetic materials in multiple layers according to an impedance matching principle. According to the method, rare earth permanent magnet alloy blocks are converted into rare earth permanent magnet alloy particles by introducing a ball milling process, electromagnetic parameters of the rare earth permanent magnet alloy particles are optimized, and the rare earth permanent magnet alloy particles are further compounded with magnetic metal micro powder, so that a heterogeneous interface is formed between a rare earth compound and the metal micro powder; impedance matching of the rare earth composite magnetic material is optimized by regulating and controlling the dielectric constant of the rare earth composite magnetic material, electromagnetic parameter regulation and control of the composite wave-absorbing material and effective improvement of the wave-absorbing performance are achieved, and finally the rare earth composite magnetic wave-absorbing material with the broadband absorption characteristic is prepared by optimizing different interlayer matching thicknesses and concentrations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave absorbing materials, and in particular relates to a rare earth composite magnetic material, a rare earth composite magnetic wave absorbing material and a preparation method thereof. Background Art

[0002] With the rapid development of electrification technology, the Internet of Things and high-speed communications, mobile phones, computers, tablets and other communication electronics have become an indispensable part of our daily lives. People's continuous demand for miniaturization, high efficiency and high frequency of electronic equipment has caused serious electromagnetic pollution and electromagnetic interference, affecting the stability of electronic equipment, electronic information security and human health. Studies have shown that people who have been in an electromagnetic radiation environment for a long time will suffer varying degrees of damage to their central nervous system, reproductive system and immune system, which will in turn cause changes in blood, lymph and cell protoplasm, and even induce leukemia, tumors and embryonic chromosome changes. At the same time, due to the presence of electromagnetic radiation, electronic equipment and communication signals will be disturbed and cannot work normally, which will also cause accidents. Therefore, the development of high-performance absorbing materials has very important economic value and practical significance for solving the problems of electromagnetic pollution and electromagnetic interference and promoting the long-term development of the electronics industry.

[0003] Ferromagnetic metal powder has become one of the most widely used and studied microwave absorbing materials due to its high saturation magnetization, magnetic permeability and Curie temperature. However, due to the high conductivity of pure ferromagnetic alloy and the large eddy current loss, the imaginary part of its magnetic permeability decreases rapidly with the increase of frequency, making it impossible to give full play to the magnetic loss characteristics of the material. At the same time, spherical ferromagnetic alloy powder is limited by the Snoek limit, resulting in low magnetic permeability, and the large dielectric constant also leads to poor impedance matching, which limits the application of ferromagnetic metal powder in the microwave field. Reducing its large dielectric constant and breaking through the Snoke limit are the key to obtaining good microwave absorption performance of ferromagnetic metal powder in the gigahertz frequency range. Common methods for reducing the dielectric constant of ferromagnetic metal powder mainly use inorganic insulating materials to coat the powder (such as MgO, SiO2), surface modification (such as phosphoric acid, silane coupling agent) and material composite (such as multi-walled carbon nanotubes, flake graphite). Although the above modification methods can improve the wave absorption performance of ferromagnetic metal powders, there are still problems such as complex preparation process and obvious decrease in magnetic permeability.

[0004] In summary, it is very necessary to provide a rare earth composite magnetic material, a rare earth composite magnetic absorbing material and a preparation method thereof. Summary of the invention

[0005] In order to solve one or more technical problems existing in the prior art, the present invention provides a rare earth composite magnetic material, a rare earth composite magnetic wave absorbing material and a preparation method thereof.

[0006] The present invention provides a rare earth composite magnetic material in a first aspect. The rare earth composite magnetic material comprises composite rare earth permanent magnet alloy particles and magnetic metal powder. The surface of the rare earth permanent magnet alloy particles is modified with oleic acid.

[0007] Preferably, the rare earth permanent magnet alloy particles are compounded with the magnetic metal powder by solvent induced dispersion.

[0008] Preferably, the rare earth permanent magnet alloy particles are MFeB, wherein M is Sm, Ce or Nd; and / or the magnetic metal powder is FeCo and / or FeSiAl. Preferably, the particle size of the magnetic metal powder is 20 to 50 μm.

[0009] In a second aspect, the present invention provides a rare earth composite magnetic absorbing material, wherein the rare earth composite magnetic absorbing material is obtained by arranging the rare earth composite magnetic material described in the first aspect of the present invention in multiple layers according to the impedance matching principle; preferably, before the multi-layer arrangement, the rare earth composite magnetic material is firstly compounded with epoxy resin to form an epoxy resin composite material, and then the epoxy resin composite material is arranged in multiple layers according to the impedance matching principle.

[0010] The present invention provides in a third aspect a method for preparing the rare earth composite magnetic wave absorbing material according to the second aspect of the present invention, the method comprising the following steps:

[0011] (1) preparing rare earth permanent magnet alloy particles with surface modification of oleic acid;

[0012] (2) compounding the rare earth permanent magnet alloy particles whose surfaces are modified with oleic acid with magnetic metal micropowders to obtain rare earth composite magnetic materials;

[0013] (3) Arranging the rare earth composite magnetic material in multiple layers according to the impedance matching principle to obtain a rare earth composite magnetic absorbing material.

[0014] Preferably, step (1) includes the following sub-steps: (11) placing the rare earth permanent magnet alloy block, oleic acid, organic solvent, and grinding balls in a ball milling jar and performing ball milling in a planetary ball mill to obtain a ball milled material; (12) performing solid-liquid separation on the ball milled material using a suction filtration funnel to obtain a precipitate, then adding an organic solvent for washing, and then filtering and separating the precipitate; (13) placing the filtered and separated precipitate in an oven to dry, to obtain rare earth permanent magnet alloy particles whose surface is modified with oleic acid.

[0015] Preferably, in step (11), the mass ratio of the rare earth permanent magnet alloy block, oleic acid, organic solvent and grinding ball is 1:(0.3-1):(0.3-2):(1-4); in step (11), the rotation speed of the ball mill is 100-800 rpm, and the time is 0.5-24 h; in step (11) and / or step (12), the organic solvent is one or more of n-heptane, ethanol and acetone; and / or in step (13), the drying temperature is 60°C-150°C, and the time is 2-24 h.

[0016] Preferably, step (2) is: dispersing the rare earth permanent magnet alloy particles with oleic acid on the surface in deionized water and / or an organic solvent, then adding magnetic metal powder and stirring evenly, and then centrifuging, washing and drying in sequence to obtain a rare earth composite magnetic material.

[0017] Preferably, in step (2): the organic solvent used to disperse the rare earth permanent magnet alloy particles whose surfaces are modified with oleic acid is ethanol and / or acetone; the mass ratio of the rare earth permanent magnet alloy particles whose surfaces are modified with oleic acid to the magnetic metal micropowder is (0-0.6):1, preferably (0.2-0.6):1; the stirring speed is 100-800 rpm, and the time is 2-24 h; the centrifugal speed is 2000-13000 rpm, and the time is 5-30 min; and / or the drying temperature is 60°C-150°C, and the time is 2-24 h.

[0018] Preferably, in step (3): the rare earth composite magnetic material is arranged in multiple layers by optimizing the matching thickness and concentration between different layers to obtain a rare earth composite magnetic absorbing material; preferably, before the multi-layer arrangement, the rare earth composite magnetic material is first compounded with epoxy resin to form an epoxy resin composite material, and then the epoxy resin composite material is arranged in multiple layers by optimizing the matching thickness and concentration between different layers.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects:

[0020] (1) The present invention proposes a rare earth composite magnetic material, a rare earth composite magnetic absorbing material and a preparation method thereof, which are used to solve the problem that ferromagnetic metal powder is limited by the Snoek limit, the impedance matching is poor due to the large dielectric constant, and the rare earth permanent magnetic material block and the high dielectric constant cannot be directly used as an absorbing material. The method of the present invention prepares rare earth permanent magnetic alloy particles by ball milling, and composites them with magnetic metal powder, preferably combining a multi-layer matching structure design to prepare a rare earth composite magnetic absorbing material. Specifically, the present invention transforms the rare earth permanent magnetic alloy block into rare earth permanent magnetic alloy particles by introducing a ball milling process and optimizes its electromagnetic parameters, and further composites it with magnetic metal powder (ferromagnetic metal powder) to form a heterogeneous interface between the rare earth compound and the metal powder, and optimizes its impedance matching by regulating the dielectric constant of the rare earth composite magnetic material, thereby achieving the electromagnetic parameter regulation of the composite absorbing material and effectively improving the absorbing performance, and finally preparing a rare earth composite magnetic absorbing material with broadband absorption characteristics by optimizing the matching thickness and concentration between different layers.

[0021] (2) The embodiment of the present invention shows that compared with the undehydrogenated SmFeB rare earth permanent magnet block material before ball milling, the particle size of the undehydrogenated SmFeB particles after ball milling is significantly reduced, the dielectric constant and magnetic permeability are reduced, and the impedance matching is enhanced. Furthermore, the present invention compounds different proportions of rare earth permanent magnet alloy particles into magnetic metal micropowders, and by adjusting the electromagnetic parameters of the magnetic metal micropowders, the absorption performance of the rare earth composite magnetic material is greatly improved. The effective absorption bandwidth of the rare earth composite magnetic material doped with 60wt% undehydrogenated SmFeB at a thickness of 2mm can reach more than 2.12GHz, and the multi-layer matching structure design results show that the rare earth composite magnetic absorbing material under the three-layer structure has the best broadband absorption performance. The method of the present invention can provide new ideas for the application of rare earth permanent magnet materials in absorbing materials, and promote the development and application of new rare earth materials in high value-added products. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1: It is the electromagnetic parameter diagram of the undehydrogenated SmFeB block before and after ball milling (during the test, the undehydrogenated SmFeB is mixed with the paraffin matrix to form a mixture, and the mass fraction of the undehydrogenated SmFeB in the mixture is 80%); in the figure, (a) is the relationship diagram of the real part of the dielectric constant (e') and the frequency (Frequency), (b) is the relationship diagram of the imaginary part of the dielectric constant (e") and the frequency (Frequency), (c) is the relationship diagram of the real part of the magnetic permeability (u') and the frequency (Frequency), (d) is the relationship diagram of the imaginary part of the magnetic permeability (u") and the frequency (Frequency);

[0024] Figure 2 It is an electromagnetic parameter diagram of rare earth composite magnetic materials composited with undehydrogenated SmFeB particles and FeSiAl in different proportions (during the test, the rare earth composite magnetic material and the paraffin matrix are mixed to form a mixture, and the mass fraction of the rare earth composite magnetic material in the mixture is 75%); in the figure, (a) is a diagram showing the relationship between the real part of the dielectric constant (e') and the frequency (Frequency), (b) is a diagram showing the relationship between the imaginary part of the dielectric constant (e") and the frequency (Frequency), (c) is a diagram showing the relationship between the real part of the magnetic permeability (u') and the frequency (Frequency), and (d) is a diagram showing the relationship between the imaginary part of the magnetic permeability (u") and the frequency (Frequency);

[0025] Figure 3 This is a graph showing the relationship between electromagnetic wave reflection loss and frequency of rare earth composite magnetic materials (single layer, thickness 2 mm) composited with undehydrogenated SmFeB particles and FeSiAl in different proportions;

[0026] Figure 4 This is a graph showing the relationship between electromagnetic wave reflection loss and frequency of a rare earth composite magnetic absorbing material (multilayer, with a total thickness of 2 mm) composited with non-dehydrogenated SmFeB particles and FeSiAl in different proportions. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Ferromagnetic metal powder (magnetic metal powder) has become one of the most widely used and studied microwave absorbing materials due to its high saturation magnetization, magnetic permeability and Curie temperature. However, due to the high electrical conductivity of pure ferromagnetic alloys and large eddy current losses, the imaginary part of its magnetic permeability decreases rapidly with increasing frequency, making it impossible to fully utilize the magnetic loss characteristics of the material. At the same time, spherical ferromagnetic alloy powders are limited by the Snoek limit, resulting in low magnetic permeability, and the large dielectric constant also leads to poor impedance matching, which limits the application of ferromagnetic metal powders in the microwave field. Reducing its large dielectric constant and breaking through the Snoke limit are the keys to obtaining good microwave absorption performance of ferromagnetic metal powders in the gigahertz (GHz) frequency range.

[0029] Rare earth permanent magnet materials are alloys formed by rare earth metals and transition metals. They are permanent magnet materials made through a certain process and have the ability to maintain strong magnetism for a long time. They have been widely used in the fields of industry, manufacturing, medical treatment, automobiles, communications, etc. The inventors have found that rare earth elements can effectively regulate the electromagnetic parameters of transition metal magnetic powders, thereby optimizing their wave absorbing performance; for example, replacing the main phase elements with large-radius rare earth ions can effectively increase the lattice constant of the wave absorbing material, induce lattice distortion, increase the imaginary part of the dielectric constant of the wave absorbing material, and optimize the dielectric loss of the wave absorbing material. At the same time, doping with a small amount of rare earth particles can improve the impedance matching of the wave absorbing material and enhance the loss capacity of the wave absorbing material to the incident electromagnetic wave. In addition, the introduction of rare earth can effectively regulate the magnetic anisotropy of the magnetic material, thereby changing the natural resonance frequency of the material and realizing the regulation of magnetic loss. However, the currently prepared rare earth permanent magnet materials generally have a large particle size and cannot be directly applied to the wave absorbing material. At the same time, the large-particle rare earth permanent magnet material itself has a high dielectric constant, which leads to poor material impedance matching and cannot achieve effective absorption of electromagnetic waves. Therefore, if the rare earth permanent magnet alloy block can be transformed into rare earth permanent magnet alloy particles and combined with magnetic metal micropowder to construct a rare earth composite magnetic material, by optimizing the electromagnetic parameters and impedance matching of the magnetic metal micropowder, it can provide new opportunities for improving the absorbing performance of the magnetic metal micropowder and the application of rare earth materials in absorbing materials.

[0030] In view of the problem that ferromagnetic metal powder is limited by Snoek limit, large dielectric constant leads to poor impedance matching, and rare earth permanent magnet material has large particle size and high dielectric constant and cannot be directly used as an absorbing material, the present invention proposes a rare earth composite magnetic material, a rare earth composite magnetic absorbing material and a preparation method thereof. The present invention first prepares rare earth permanent magnet alloy particles by ball milling, then uses solvent induced dispersion to composite the rare earth permanent magnet alloy particles with magnetic metal powder to obtain a rare earth composite magnetic material, and finally combines a multi-layer matching structure design to prepare a rare earth composite magnetic absorbing material.

[0031] The present invention provides a rare earth composite magnetic material in a first aspect. The rare earth composite magnetic material comprises composite rare earth permanent magnet alloy particles and magnetic metal powder. The surface of the rare earth permanent magnet alloy particles is modified with oleic acid (oleic acid molecules).

[0032] According to some preferred embodiments, the rare earth permanent magnet alloy particles are composited (uniformly mixed) with the magnetic metal fine powder by solvent-induced dispersion.

[0033] According to some preferred embodiments, the rare earth permanent magnet alloy particles are MFeB, wherein M is Sm (samarium), Ce (cerium) or Nd (neodymium); and / or the magnetic metal powder is FeCo and / or FeSiAl, preferably, the particle size of the magnetic metal powder is 20 to 50 μm.

[0034] In a second aspect, the present invention provides a rare earth composite magnetic absorbing material, wherein the rare earth composite magnetic absorbing material is obtained by arranging the rare earth composite magnetic material described in the first aspect of the present invention in multiple layers according to the impedance matching principle (impedance matching design principle); preferably, before the multi-layer arrangement, the rare earth composite magnetic material is first compounded with epoxy resin to form an epoxy resin composite material, and then the epoxy resin composite material is arranged in multiple layers according to the impedance matching principle.

[0035] The present invention provides in a third aspect a method for preparing the rare earth composite magnetic wave absorbing material according to the second aspect of the present invention, the method comprising the following steps:

[0036] (1) preparing rare earth permanent magnet alloy particles with surface modification of oleic acid;

[0037] (2) Compounding the rare earth permanent magnet alloy particles whose surfaces are modified with oleic acid with magnetic metal powder (ferromagnetic metal powder) to obtain a rare earth composite magnetic material; in the present invention, for example, the rare earth permanent magnet alloy particles whose surfaces are modified with oleic acid are compounded with the magnetic metal powder by solvent-induced dispersion;

[0038] (3) arranging the rare earth composite magnetic material in multiple layers according to the impedance matching principle (impedance matching design principle) to obtain a rare earth composite magnetic absorbing material; in the present invention, the impedance matching principle is specifically to optimize the matching thickness between different layers and the concentration of the rare earth composite magnetic material between the layers;

[0039] The present invention first uses a ball milling process to transform large-size rare earth permanent magnetic materials into rare earth permanent magnetic powders (rare earth permanent magnetic alloy particles) and optimizes their electromagnetic properties. Furthermore, rare earth permanent magnetic powders are introduced into ferromagnetic metal powders to form a heterogeneous interface between rare earth compounds and metal powders, and the impedance matching characteristics of rare earth magnetic composite absorbing materials are optimized by regulating the dielectric constant. At the same time, the interaction between rare earth elements and the outer electrons of metal magnetic powders is used to regulate the magnetic permeability of alloy particles, so as to achieve effective optimization of electromagnetic parameter regulation and absorbing performance of composite absorbing materials, and finally prepare broadband response absorbing materials by optimizing the matching thickness and concentration between different layers. The method of the present invention can provide a design basis and theoretical guidance for the rational construction of rare earth composite magnetic absorbing materials, and promote the high-quality development of the rare earth new materials industry.

[0040] According to some preferred embodiments, step (1) comprises the following sub-steps:

[0041] (11) placing a rare earth permanent magnet alloy block, oleic acid, an organic solvent (e.g., n-heptane), and a grinding ball (e.g., a steel ball) in a ball milling jar and milling them in a planetary ball mill to obtain a ball milled material; the present invention does not specifically limit the source or preparation process of the rare earth permanent magnet alloy block, for example, a dehydrogenated MFeB block prepared by a dehydrogenation process or a non-dehydrogenated MFeB block prepared by a non-dehydrogenation process can be used; wherein M is Sm (samarium), Ce (cerium), or Nd (neodymium);

[0042] (12) using a suction filter funnel to separate the ball milled material into solid and liquid to obtain a precipitate, then adding an organic solvent (such as n-heptane, ethanol, acetone, etc.) to wash the precipitate, and then filtering the precipitate to separate the precipitate;

[0043] (13) The precipitate separated by filtration is placed in an oven for drying to obtain rare earth permanent magnet alloy particles with oleic acid modified on the surface.

[0044] In the present invention, the rare earth permanent magnet alloy particles with oleic acid surface modification and magnetic metal powder are used for compounding. This is because the present invention finds that oleic acid can form a hydrophobic coating on the surface of the rare earth permanent magnet alloy particles, improve its dispersibility, enable it to be more evenly mixed with ferromagnetic metal powder, improve the surface stability and dispersibility of the particles, reduce the aggregation phenomenon between particles, and optimize the distribution and interaction of particles. This can improve the electromagnetic wave absorption capacity of the material and optimize the impedance matching performance; in addition, the surface modified oleic acid can not only improve the dispersibility and interface stability of the particles, but also form a certain electromagnetic barrier effect between the particles. Oleic acid modification enhances the interface effect between the rare earth permanent magnet alloy particles and the ferromagnetic metal powder, improves the electromagnetic wave absorption capacity of the interface area, and enhances the broadband characteristics and absorbing performance of the absorbing material. Therefore, the present invention converts the large-particle-size rare earth permanent magnet material into fine particles through a ball milling process and performs oleic acid surface modification and ferromagnetic metal powder compounding method, which not only optimizes the impedance matching characteristics, but also significantly improves the broadband absorbing performance of the absorbing material.

[0045] According to some preferred embodiments, in step (11), the mass ratio of the rare earth permanent magnet alloy block, oleic acid, organic solvent, and grinding ball is 1:(0.3-1):(0.3-2):(1-4); in the present invention, preferably, the mass ratio of the rare earth permanent magnet alloy block to the oleic acid is 1:(0.3-1) (for example, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1); the present invention finds that if less than 0.3:1 oleic acid is added during the ball milling process, the broadband absorbing performance of the absorbing material obtained by compounding the oleic acid with the ferromagnetic metal powder cannot be effectively improved due to the small amount of oleic acid used. This is because the present invention uses the long chain of oleic acid to obtain the absorbing material. The hydrophobic carbon chain part covers the surface of the rare earth permanent magnet alloy particles to form a hydrophobic protective layer of appropriate thickness to enhance the interface effect between the rare earth permanent magnet alloy particles and the ferromagnetic metal powder, improve the electromagnetic wave absorption capacity of the interface area, and enhance the broadband characteristics of the absorbing material; in addition, the present invention finds that if the amount of oleic acid used is too much, it may cause the oleic acid molecules to form an overly thick coating layer on the surface of the rare earth permanent magnet alloy particles. The overly thick oleic acid layer will hinder the effective magnetic coupling and physical effect between the particles, and may cause problems such as poor impedance matching, weakened magnetic loss and electrical loss effects, and poor material stability, thereby affecting the overall magnetic loss and absorbing performance of the finally prepared rare earth composite magnetic material and rare earth composite magnetic absorbing material.

[0046] According to some preferred embodiments, in step (11), the rotation speed of the ball mill is 100-800 rpm (e.g., 100, 200, 300, 400, 500, 600, 700 or 800 rpm), and the time is 0.5-24 h (e.g., 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24 h); in step (11) and / or step (12), , the organic solvent is one or more of n-heptane, ethanol, and acetone; and / or in step (13), the drying temperature is 60°C to 150°C (for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, or 150°C), and the drying time is 2 to 24 h (for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, or 24 h).

[0047] According to some specific embodiments, the preparation of the rare earth permanent magnet alloy particles modified with oleic acid on the surface is as follows: placing a rare earth permanent magnet alloy block, oleic acid, an organic solvent (such as n-heptane), and a grinding ball (such as a steel ball) in a ball mill according to a certain weight ratio, and the mass ratio of the rare earth permanent magnet alloy block: oleic acid: organic solvent: grinding ball is 1:0.3~1:0.3~2:1~4; the material is ball milled in a planetary ball mill at a specific speed for a certain time, wherein the speed is 100~800rpm, and the time is 0.5~24h; the ball milled material is filtered with a suction funnel A precipitate is obtained by solid-liquid separation, and an organic solvent (such as n-heptane, ethanol, acetone, etc.) is added for washing, and then the precipitate is separated by suction filtration; the precipitate separated by suction filtration is placed in an oven for drying to obtain rare earth permanent magnet alloy particles with surface modified with oleic acid, wherein the drying temperature is 60°C to 150°C and the time is 2 to 24 hours; during the washing process, the free oleic acid molecules will be washed away by the solvent, while the oleic acid modified on the surface of the rare earth permanent magnet alloy particles is firmly adsorbed on the outer surface of the particles to form a modified layer due to the coordination interaction between the metal and the carboxylate, and is not easily washed away by the solvent.

[0048] According to some preferred embodiments, step (2) is: dispersing the rare earth permanent magnet alloy particles with oleic acid on the surface in deionized water and / or an organic solvent, then adding magnetic metal micropowder and stirring evenly, and then centrifuging, washing and drying in sequence to obtain a rare earth composite magnetic material.

[0049] According to some preferred embodiments, in step (2): the organic solvent used to disperse the rare earth permanent magnet alloy particles with oleic acid on the surface is ethanol and / or acetone; the mass ratio of the rare earth permanent magnet alloy particles with oleic acid on the surface to the magnetic metal powder is (0-0.6):1, preferably (0.2-0.6):1 (for example, 0.2:1, 0.3:1, 0.4:1, 0.5:1 or 0.6:1); in the present invention, preferably, the rare earth permanent magnet alloy particles with oleic acid on the surface are The mass ratio of gold particles to the magnetic metal powder is (0-0.6): 1. The present invention finds that if the doping ratio of the rare earth permanent magnet alloy particles modified with oleic acid on the surface is too high, the magnetic permeability of the magnetic metal powder will be reduced, thereby reducing the magnetic loss of the rare earth composite magnetic material and reducing the impedance matching, which will in turn lead to a decrease in the wave absorbing performance; the stirring speed is 100-800rpm (for example, 100, 200, 300, 400, 500, 600, 700 or 800rpm), The time is 2 to 24 hours (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24 hours); the speed of the centrifuge is 2000 to 13000 rpm (e.g., 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 11000, 12000 or 13000 rpm), and the time is 5 to 3 0min (e.g. 5, 10, 15, 20, 25 or 30min); and / or the drying temperature is 60°C to 150°C (e.g. 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C), and the time is 2 to 24h (e.g. 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24h).

[0050] According to some specific embodiments, the rare earth composite magnetic material is prepared as follows: the obtained rare earth permanent magnet alloy particles with oleic acid on the surface are dispersed in deionized water or an organic solvent (such as ethanol, acetone), and then magnetic metal powder is added, and the mixture is fully mixed and stirred, the mass ratio of rare earth permanent magnet alloy particles: magnetic metal powder is 0-0.6:1, the stirring speed is 100-800rpm, and the time is 2-24h; then a precipitate is obtained by centrifugal separation, deionized water or an organic solvent (such as ethanol, acetone) is added to the precipitate for washing, and then the precipitate is centrifuged again, wherein the centrifugal separation speed is 2000-13000rpm, and the time is 5-30min; finally, the obtained precipitate is placed in an oven and dried to obtain a rare earth composite magnetic material, the drying temperature is 60°C-150°C, and the time is 2-24h.

[0051] According to some preferred embodiments, step (2) is: dispersing the rare earth permanent magnet alloy particles modified with oleic acid on the surface in deionized water and / or an organic solvent, then adding magnetic metal powder and stirring evenly, and then centrifuging, washing, drying and gradient annealing in sequence to obtain a rare earth composite magnetic material; in the present invention, the gradient annealing treatment is: first annealing at 200-300°C for 15-30min, then annealing at 300-500°C for 15-30min, and finally naturally cooling to room temperature; the gradient annealing treatment is carried out under vacuum conditions, for example, under vacuum conditions with a pressure of 200-500Pa; the present invention is preferably further carried out to obtain the rare earth composite magnetic material by the gradient annealing treatment, by gradually optimizing the microstructure, interface properties and magnetic properties of the composite material of the rare earth permanent magnet alloy particles and the magnetic metal powder, thereby facilitating the improvement of the material's absorption The present invention is beneficial to optimizing the wave absorption performance and broadband absorption performance of rare earth composite magnetic materials by performing the gradient annealing treatment. The possible reason is that the present invention first performs a short-time annealing treatment at a low temperature stage, which can effectively remove the internal stress of the material, optimize the dispersibility and surface characteristics of the particles, and retain the surface modification effect of oleic acid. The lubrication and surface activity of oleic acid are used to help optimize the interaction force between particles, thereby improving the magnetic coupling and electromagnetic wave absorption effect of the particles in the composite material. Then, a short-time annealing treatment is performed at a high temperature stage, and part of the oleic acid may decompose, but this part of the oleic acid decomposition products can also play a role in further enhancing the interaction force between the particles, so that the contact force between the particles is further enhanced, which is beneficial to improving the magnetic coupling effect of the particles in the composite material, enhancing the magnetic loss and magnetic permeability, and the enhanced magnetic coupling effect is beneficial to improving the wave absorption performance and broadband wave absorption ability of the material.

[0052] According to some preferred embodiments, in step (3): the rare earth composite magnetic material is subjected to multi-layer structure design (multi-layer arrangement) by optimizing the matching thickness and concentration between different layers (i.e., according to a certain concentration and thickness) to obtain a rare earth composite magnetic absorbing material; preferably, before the multi-layer arrangement, the rare earth composite magnetic material is first compounded (uniformly mixed) with epoxy resin to form an epoxy resin composite material, and then the epoxy resin composite material is subjected to multi-layer arrangement by optimizing the matching thickness and concentration between different layers; specifically, in the multi-layer structure design, each layer is an epoxy resin composite material formed by compounding the rare earth composite magnetic material and the epoxy resin, and the rare earth composite magnetic material is in the epoxy resin composite material. The mass fraction (filling amount) is 70-80wt%, preferably 75wt%, and the doping amount of the rare earth permanent magnet alloy particles with oleic acid on the surface in the rare earth composite magnetic material contained in the epoxy resin composite material in each layer of the structure decreases successively from top to bottom; the thickness of the epoxy resin composite material in each layer of the structure is the same or different. When the thickness of the epoxy resin composite material in each layer of the structure is different, the thickness of the epoxy resin composite material located in the upper layer is not less than the thickness of the epoxy resin composite material located in the lower layer; the present invention does not specifically limit the type of epoxy resin used in the composite, and technicians in this field can use any type of epoxy resin suitable for absorbing materials, and those skilled in the art can make a routine selection.

[0053] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and deformations according to the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention. The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples and comparative examples, unless otherwise specified, can all be obtained from commercial channels.

[0054] In order to verify the applicability of ball milling and surface modification of oleic acid to regulate the electromagnetic parameters of rare earth permanent magnet alloy blocks, the present invention selected typical rare earth permanent magnet alloy materials (non-dehydrogenated cerium iron boron, non-dehydrogenated samarium iron boron, dehydrogenated samarium iron boron, non-dehydrogenated neodymium iron boron, dehydrogenated neodymium iron boron) for research:

[0055] Preparation of rare earth permanent magnet alloy particles with oleic acid on the surface:

[0056] Undehydrogenated cerium iron boron (undehydrogenated CeFeB) particles with surface modification of oleic acid: add 10g of n-heptane to a 150mL beaker, then add 10g of oleic acid, stir thoroughly until dissolved, add 40g of steel ball to the beaker, then add 20g of undehydrogenated cerium iron boron bulk sample to the beaker, stir to mix thoroughly, then add the mixed sample in the beaker to a 100mL ball mill, and mill in a planetary ball mill at a speed of 400rpm for 2h. After the milling, place the mixture (ball milled material) in a sand core funnel (suction funnel), separate the solid precipitate by suction filtration with a water pump, then wash the sample thoroughly with n-heptane, then separate the precipitate by suction filtration and place it in an oven at 80°C for 6h to obtain undehydrogenated cerium iron boron particles with surface modification of oleic acid.

[0057] Undehydrogenated SmFeB particles modified with oleic acid on the surface: 10 g of n-heptane was added to a 150 mL beaker, followed by 10 g of oleic acid, stirred thoroughly until dissolved, 40 g of steel balls were added to the beaker, and then 20 g of undehydrogenated SmFeB bulk sample was added to the beaker, stirred to mix thoroughly, and then the mixed sample in the beaker was added to a 100 mL ball milling jar, and ball milled in a planetary ball mill at a speed of 400 rpm for 2 h. After the end, the mixture ( The ball-milled material) is placed in a sand core funnel (suction funnel), and the solid precipitate is separated by suction filtration through a water pump, and then the sample is fully washed with n-heptane, and then the precipitate is separated by suction filtration and placed in an oven at 80°C for insulation and drying for 6 hours to obtain non-dehydrogenated samarium iron boron particles with oleic acid modified on the surface; the non-dehydrogenated samarium iron boron particles with oleic acid modified on the surface (non-dehydrogenated samarium iron boron rare earth permanent magnet alloy particles with oleic acid modified on the surface) used in the following embodiments of the present invention are all prepared under such conditions unless otherwise specified.

[0058] Dehydrogenated samarium iron boron (dehydrogenated SmFeB) particles with oleic acid surface modified: add 10g of n-heptane to a 150mL beaker, then add 10g of oleic acid, stir thoroughly until dissolved, add 40g of steel ball to the beaker, then add 20g of dehydrogenated samarium iron boron block sample to the beaker, stir to mix thoroughly, then add the mixed sample in the beaker to a 100mL ball mill, and mill in a planetary ball mill at a speed of 400rpm for 2h. After the milling, place the mixture (ball milled material) in a sand core funnel (suction funnel), separate the solid precipitate by suction filtration with a water pump, then wash the sample thoroughly with n-heptane, then separate the precipitate by suction filtration and place it in an oven at 80°C for 6h to obtain dehydrogenated samarium iron boron particles with oleic acid surface modified.

[0059] Undehydrogenated NdFeB (undehydrogenated NdFeB) particles with surface modification of oleic acid: add 10g of n-heptane to a 150mL beaker, then add 10g of oleic acid, stir thoroughly until dissolved, add 40g of steel ball to the beaker, then add 20g of undehydrogenated NdFeB bulk sample to the beaker, stir to mix thoroughly, then add the mixed sample in the beaker to a 100mL ball mill, and mill in a planetary ball mill at a speed of 400rpm for 2h. After the milling, place the mixture (ball milled material) in a sand core funnel (suction funnel), separate the solid precipitate by suction filtration with a water pump, then wash the sample thoroughly with n-heptane, then separate the precipitate by suction filtration and place it in an oven at 80°C for 6h to obtain undehydrogenated NdFeB particles with surface modification of oleic acid.

[0060] Dehydrogenated NdFeB (dehydrogenated NdFeB) particles with surface modification of oleic acid: add 10g of n-heptane to a 150mL beaker, then add 10g of oleic acid, stir thoroughly until dissolved, add 40g of steel ball to the beaker, then add 20g of dehydrogenated NdFeB block sample to the beaker, stir to mix thoroughly, then add the mixed sample in the beaker to a 100mL ball mill, and mill in a planetary ball mill at a speed of 400rpm for 2h. After the milling, place the mixture (ball milled material) in a sand core funnel (suction funnel), separate the solid precipitate by suction filtration with a water pump, then wash the sample thoroughly with n-heptane, then separate the precipitate by suction filtration and place it in an oven at 80°C for 6h to obtain dehydrogenated NdFeB particles with surface modification of oleic acid.

[0061] The electromagnetic parameters of the undehydrogenated samarium iron boron block before ball milling and the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles with oleic acid modified on the surface obtained after ball milling are as follows: Figure 1 As shown in the figure, the real part of the dielectric constant of the undehydrogenated SmFeB block before ball milling is about 15 at 2-10 GHz, which increases rapidly to 38 at around 11 GHz, and then slowly decreases. The imaginary part of the dielectric constant is wavy, and there is an obvious absorption peak at a specific electromagnetic wave position. After 2 hours of ball milling, the real part of the dielectric constant of the undehydrogenated SmFeB rare earth permanent magnet alloy particles with oleic acid on the surface is basically maintained at about 15, and the amplitude of change with the electromagnetic wave frequency is not large. Compared with the initial unmilled sample, the dielectric constant in the high-frequency band is significantly reduced, and the imaginary part of the dielectric constant decreases significantly relative to the initial overall, and the absorption peak position and size change. The dielectric loss tangent values ​​before and after ball milling are all lower than 0.4. Similar to the dielectric constant, the real part of the magnetic permeability becomes more stable after ball milling, the imaginary part of the magnetic permeability decreases slightly, and the absorption peak intensity at 9 GHz is significantly enhanced. The results show that the ball milling process used in the present invention can reduce the particle size of the rare earth permanent magnet alloy block while optimizing its electromagnetic parameters, and improve its electromagnetic wave absorption capacity by enhancing impedance matching.

[0062] The present invention uses the undehydrogenated cerium iron boron, dehydrogenated samarium iron boron, undehydrogenated neodymium iron boron, dehydrogenated neodymium iron boron before ball milling, and the undehydrogenated cerium iron boron particles with oleic acid modified on the surface, the dehydrogenated samarium iron boron particles with oleic acid modified on the surface, the undehydrogenated neodymium iron boron particles with oleic acid modified on the surface, and the dehydrogenated neodymium iron boron particles with oleic acid modified on the surface. The mean of the real part of the dielectric constant, the mean of the imaginary part of the dielectric constant, the mean of the real part of the magnetic permeability, and the mean of the imaginary part of the magnetic permeability are shown in Table 1. It can be seen that the real and imaginary part values ​​of the dielectric constant of the rare earth permanent magnet alloy particles after ball milling are significantly reduced compared with those before ball milling, the real part of the magnetic permeability is basically increased, and the imaginary part of the magnetic permeability does not change much. These results show that by ball milling process and controlling ball milling process parameters, the electromagnetic parameter regulation of rare earth permanent magnet alloy powder can be realized, and then rare earth permanent magnet alloy particles with better wave absorption performance can be obtained.

[0063] Table 1: Average electromagnetic parameters of other types of rare earth permanent magnet alloy blocks before and after ball milling

[0064]

[0065]

[0066] 0-12g of undehydrogenated samarium iron boron rare earth permanent magnet alloy particles (referred to as undehydrogenated SmFeB particles) prepared according to the above conditions and modified with oleic acid on the surface are added to a 150mL beaker, 50mL of ethanol is added as a dispersant, and stirred evenly, then 20g of FeSiAl magnetic metal powder (referred to as FeSiAl) is added to the beaker and stirred at room temperature for 12h, the stirring rate is 400rpm, and the FeSiAl powder and the rare earth permanent magnet alloy particles modified with oleic acid on the surface are uniformly composited by van der Waals force and electrostatic interaction. After stirring, the precipitate is centrifuged at a speed of 5000rpm for 5min, ethanol is added for washing and centrifuged again (5000rpm for 5min), and the precipitate obtained by centrifugation is placed in an oven for drying at a drying temperature of 75°C for 4h to obtain rare earth composite magnetic materials with different proportions of undehydrogenated SmFeB particles and FeSiAl, as shown in the following Examples 1 to 7.

[0067] Example 1

[0068] Add 20g of FeSiAl magnetic metal powder into a 150mL beaker, add 50mL of ethanol as a dispersant, stir at room temperature for 12h, and the stirring rate is 400rpm. After the stirring is completed, centrifuge to separate the precipitate at a speed of 5000rpm for 5min, add ethanol for washing and centrifuge again (speed of 5000rpm for 5min), and place the precipitate obtained by centrifugation in an oven to dry at a drying temperature of 75°C for 4h to obtain a rare earth magnetic material (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 0%).

[0069] Example 2

[0070] 4 g of undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface were added into a 150 mL beaker, 50 mL of ethanol was added as a dispersant, and after stirring evenly, 20 g of FeSiAl magnetic metal powder was added and stirred at room temperature for 12 hours at a stirring rate of 400 rpm. After stirring, the precipitate was separated by centrifugation at a speed of 5000 rpm for 5 minutes, ethanol was added for washing and centrifuged again (at a speed of 5000 rpm for 5 minutes), and the precipitate obtained by centrifugation was placed in an oven for drying at a drying temperature of 75°C for 4 hours to obtain a rare earth composite magnetic material (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface was 20%).

[0071] Example 3

[0072] 8 g of undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface were added into a 150 mL beaker, 50 mL of ethanol was added as a dispersant, and after stirring evenly, 20 g of FeSiAl magnetic metal powder was added and stirred at room temperature for 12 hours at a stirring rate of 400 rpm. After stirring, the precipitate was separated by centrifugation at a speed of 5000 rpm for 5 minutes, ethanol was added for washing and centrifuged again (at a speed of 5000 rpm for 5 minutes), and the precipitate obtained by centrifugation was placed in an oven for drying at a drying temperature of 75°C for 4 hours to obtain a rare earth composite magnetic material (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 40%).

[0073] Example 4

[0074] 10g of undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface were added into a 150mL beaker, 50mL of ethanol was added as a dispersant, and after stirring evenly, 20g of FeSiAl magnetic metal powder was added and stirred at room temperature for 12h, and the stirring rate was 400rpm. After stirring, the precipitate was separated by centrifugation at a speed of 5000rpm for 5min, ethanol was added for washing and centrifugation again (speed of 5000rpm for 5min), and the precipitate obtained by centrifugation was placed in an oven for drying at a drying temperature of 75°C for 4h to obtain a rare earth composite magnetic material (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface was 50%).

[0075] Example 5

[0076] 12g of undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface were added into a 150mL beaker, 50mL of ethanol was added as a dispersant, and after stirring evenly, 20g of FeSiAl magnetic metal powder was added and stirred at room temperature for 12h, and the stirring rate was 400rpm. After stirring, the precipitate was separated by centrifugation at a speed of 5000rpm for 5min, ethanol was added for washing and centrifuged again (speed of 5000rpm for 5min), and the precipitate obtained by centrifugation was placed in an oven for drying at a drying temperature of 75°C for 4h to obtain a rare earth composite magnetic material (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface was 60%).

[0077] The electromagnetic parameters of the rare earth composite magnetic materials obtained by the above-mentioned Examples 1 to 5 and the composites of the non-dehydrogenated SmFeB particles and FeSiAl in different proportions are as follows: Figure 2 As shown in the figure, it can be seen that the introduction of undehydrogenated SmFeB particles modified with oleic acid on the surface can significantly reduce the real and imaginary parts of the dielectric constant of FeSiAl, thereby optimizing its impedance matching. At the same time, with the increase of the doping amount, the electromagnetic parameters of FeSiAl show a gradual downward trend, indicating that the composite of different proportions of rare earth permanent magnet alloy particles can regulate the electromagnetic parameters of magnetic metal micropowders and effectively improve the wave absorption performance.

[0078] The relationship between the single-layer electromagnetic wave reflection loss and the frequency of the rare earth composite magnetic material of the non-dehydrogenated SmFeB particles and FeSiAl in different proportions obtained in the above-mentioned Examples 1 to 5 of the present invention is shown in the figure Figure 3 As shown, during the test, the rare earth composite magnetic materials in each embodiment are respectively compounded with epoxy resin to form epoxy resin composite materials, and the mass fraction of the rare earth composite magnetic materials in each embodiment in the epoxy resin composite material is 75% (filling amount is 75wt%); Figure 3It can be seen that at a thickness of 2 mm, the overall wave absorption performance of the FeSiAl micropowder (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 0%) is poor, and the minimum reflection loss at 2.6 GHz is -7 dB, and as the frequency increases, its reflection loss tends to gradually increase, and the wave absorption performance gradually deteriorates. For the FeSiAl micropowder composited with undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface, its reflection loss increases with the increase of the doping amount, and the wave absorption performance steadily improves, and at the same time, it exhibits better broadband absorption characteristics. At a doping amount of 60 wt% undehydrogenated samarium iron boron (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 60%), the minimum reflection loss of the rare earth composite magnetic material is -12 dB, and the effective absorption bandwidth is 2.12 GHz (the absorption bandwidth with reflection loss not greater than -10 dB), which significantly improves the wave absorption performance of the initial FeSiAl magnetic alloy micropowder. The results show that the introduction of rare earth permanent magnet alloy particles can greatly enhance the absorbing performance of magnetic metal powders, while optimizing their absorbing bandwidth to achieve absorption in a wide frequency range of 2 to 18 GHz, rather than being limited to low-frequency absorption. At the same time, the absorption peak position can be controlled by varying the doping ratio, which can guide the design of absorbing materials in different frequency bands.

[0079] Example 6

[0080] 16 g of undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface were added into a 150 mL beaker, 50 mL of ethanol was added as a dispersant, and after stirring evenly, 20 g of FeSiAl magnetic metal powder was added and stirred at room temperature for 12 hours at a stirring rate of 400 rpm. After stirring, the precipitate was separated by centrifugation at a speed of 5000 rpm for 5 minutes, ethanol was added for washing and centrifuged again (at a speed of 5000 rpm for 5 minutes), and the precipitate obtained by centrifugation was placed in an oven for drying at a drying temperature of 75°C for 4 hours to obtain a rare earth composite magnetic material (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 80%).

[0081] This embodiment also tests the relationship between the single-layer electromagnetic wave reflection loss and frequency of the rare earth composite magnetic material at a doping amount of 80wt% undehydrogenated samarium iron boron (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 80%). During the test, the rare earth composite magnetic material in this embodiment is compounded with epoxy resin to form an epoxy resin composite material, and the mass fraction of the rare earth composite magnetic material in this embodiment in the epoxy resin composite material is 75% (filling amount is 75wt%); at a thickness of 2mm, the minimum reflection loss of the rare earth composite magnetic material is measured to be -11.5dB, and the effective absorption bandwidth is 1.5GHz (the absorption bandwidth where the reflection loss is not greater than -10dB).

[0082] Example 7

[0083] 12g of undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface were added to a 150mL beaker, 50mL of ethanol was added as a dispersant, and after stirring evenly, 20g of FeSiAl magnetic metal powder was added and stirred at room temperature for 12h at a stirring rate of 400rpm. After stirring, the precipitate was separated by centrifugation at a speed of 5000rpm for 5min, ethanol was added for washing and centrifugation was performed again (speed of 5000rpm for 5min), and the centrifuged precipitate was separated by centrifugation. The precipitate obtained by separation is placed in an oven to be dried at a drying temperature of 75°C for 4 hours, and then subjected to gradient annealing treatment to obtain a rare earth composite magnetic material (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 60%); wherein the gradient annealing treatment is: first annealing at 260°C for 20 minutes, then annealing at 400°C for 20 minutes, the heating rate of the annealing treatment is 5°C / min, and finally naturally cooled to room temperature; the gradient annealing treatment is carried out under vacuum conditions.

[0084] This embodiment also tests the relationship between the single-layer electromagnetic wave reflection loss and frequency of the rare earth composite magnetic material obtained in this embodiment. During the test, the rare earth composite magnetic material in this embodiment is also compounded with epoxy resin to form an epoxy resin composite material, and the mass fraction of the rare earth composite magnetic material in this embodiment in the epoxy resin composite material is 75% (filling amount is 75wt%); at a thickness of 2mm, the minimum reflection loss of the rare earth composite magnetic material is measured to be -15.2dB, and the effective absorption bandwidth is 2.7GHz (the reflection loss is not greater than the absorption bandwidth of -10dB).

[0085] Comparative Example 1

[0086] Comparative Example 1 is substantially the same as Example 5, except that:

[0087] The preparation method of the undehydrogenated samarium iron boron (undehydrogenated SmFeB) rare earth permanent magnet alloy particles with surface modified with oleic acid used in this comparative example is as follows: 10g of n-heptane is added to a 150mL beaker, and then 3g of oleic acid is added, and the mixture is stirred thoroughly until dissolved. 40g of steel balls are added to the beaker, and then 20g of undehydrogenated samarium iron boron bulk sample is added to the beaker, and the mixture is stirred to be thoroughly mixed. Then, the mixed sample in the beaker is added to a 100mL ball mill, and the mixture is milled in a planetary ball mill at a speed of 400rpm for 2h. After the milling, the mixture (ball milled material) is placed in a sand core funnel (suction funnel), and the solid precipitate is separated by suction by a water pump. Then, the sample is fully washed with n-heptane, and then the precipitate is separated by suction and placed in an oven at 80°C for insulation and drying for 6h to obtain undehydrogenated samarium iron boron rare earth permanent magnet alloy particles with surface modified with oleic acid.

[0088] This comparative example also tests the relationship between the single-layer electromagnetic wave reflection loss and frequency of the rare earth composite magnetic material obtained in this comparative example. During the test, the rare earth composite magnetic material in this comparative example is compounded with epoxy resin to form an epoxy resin composite material, and the mass fraction of the rare earth composite magnetic material in this comparative example in the epoxy resin composite material is 75% (filling amount is 75wt%). The minimum reflection loss of the rare earth composite magnetic material obtained in this comparative example at a thickness of 2mm is measured to be -10.5dB, and the effective absorption bandwidth is 0.8GHz (the absorption bandwidth where the reflection loss is not greater than -10dB).

[0089] Comparative Example 2

[0090] Comparative Example 2 is substantially the same as Example 5, except that:

[0091] The preparation method of the non-dehydrogenated samarium iron boron (non-dehydrogenated SmFeB) rare earth permanent magnet alloy particles with surface modified with oleic acid used in this comparative example is as follows: 10g of n-heptane is added to a beaker, followed by adding 60g of oleic acid, and stirring thoroughly until the mixture is uniformly mixed; 40g of steel balls are added to the beaker, and then 20g of non-dehydrogenated samarium iron boron bulk sample is added to the beaker, and stirring is performed to fully mix the mixture; then the mixed sample in the beaker is added to a ball mill, and ball milled in a planetary ball mill at a speed of 400rpm for 2h. After the milling, the mixture (ball milled material) is placed in a sand core funnel (suction funnel), and the solid precipitate is separated by suction by a water pump; then the sample is fully washed with n-heptane, and then the precipitate is separated by suction and placed in an oven at 80°C for insulation and drying for 6h to obtain non-dehydrogenated samarium iron boron rare earth permanent magnet alloy particles with surface modified with oleic acid.

[0092] This comparative example also tests the relationship between the single-layer electromagnetic wave reflection loss and frequency of the rare earth composite magnetic material obtained in this comparative example. During the test, the rare earth composite magnetic material in this comparative example is compounded with epoxy resin to form an epoxy resin composite material, and the mass fraction of the rare earth composite magnetic material in this comparative example in the epoxy resin composite material is 75% (filling amount is 75wt%). The minimum reflection loss of the rare earth composite magnetic material obtained in this comparative example at a thickness of 2mm is measured to be -11.8dB, and the effective absorption bandwidth is 2.0GHz (the absorption bandwidth where the reflection loss is not greater than -10dB).

[0093] In order to further improve the absorption bandwidth and absorption performance of the absorbing material, the rare earth composite magnetic material obtained by combining different proportions of undehydrogenated samarium iron boron with FeSiAl magnetic powder was designed with a multilayer structure according to the impedance matching design principle to prepare the rare earth composite magnetic absorbing material.

[0094] Example 8

[0095] A two-layer rare earth composite magnetic absorbing material is provided, wherein the lower layer structure is an epoxy resin composite material formed by compounding the rare earth composite magnetic material in Example 2 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 20wt%) as a functional filler with epoxy resin, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 1mm, and the upper layer structure is an epoxy resin composite material formed by compounding the rare earth composite magnetic material in Example 5 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 60wt%) as a functional filler with epoxy resin, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 1mm.

[0096] Example 9

[0097] A rare earth composite magnetic absorbing material with a three-layer structure is provided, wherein the lower layer structure is an epoxy resin composite material formed by combining the rare earth composite magnetic material in Example 2 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 20wt%) as a functional filler with epoxy resin, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 0.6mm, the middle layer structure is an epoxy resin composite material formed by combining the rare earth composite magnetic material in Example 3 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 40wt%) as a functional filler with epoxy resin, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 0.6mm, and the upper layer structure is an epoxy resin composite material formed by combining the rare earth composite magnetic material in Example 5 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 60wt%) as a functional filler with epoxy resin, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 0.8mm.

[0098] Example 10

[0099] A rare earth composite magnetic absorbing material with a four-layer structure is provided, wherein the bottom layer structure is an epoxy resin composite material formed by compounding the rare earth composite magnetic material in Example 2 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 20wt%) as a functional filler with epoxy resin, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 0.5mm, and the penultimate layer structure is an epoxy resin composite material formed by compounding the rare earth composite magnetic material in Example 3 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 40wt%) as a functional filler with epoxy resin, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 0.5mm. 5wt%, with a thickness of 0.5mm. The third-to-last layer structure is an epoxy resin composite material formed by combining the rare earth composite magnetic material in Example 4 (the doping amount of non-dehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 50wt%) as a functional filler with epoxy resin. The filling amount of rare earth composite magnetic material is 75wt%, and the thickness is 0.5mm. The upper structure is an epoxy resin composite material formed by combining the rare earth composite magnetic material in Example 5 (the doping amount of non-dehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 60wt%) as a functional filler with epoxy resin. The filling amount of rare earth composite magnetic material is 75wt%, and the thickness is 0.5mm.

[0100] Embodiment 11

[0101] A five-layer rare earth composite magnetic absorbing material is provided, wherein the bottom layer structure is an epoxy resin composite material formed by the rare earth magnetic material in Example 1 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 0wt%) as a functional filler and epoxy resin, the rare earth magnetic material filling amount is 75wt%, and the thickness is 0.4mm, the second-to-last layer structure is an epoxy resin composite material formed by the rare earth composite magnetic material in Example 2 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 20wt%) as a functional filler and epoxy resin, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 0.4mm, the third-to-last layer structure is an epoxy resin composite material formed by the rare earth composite magnetic material in Example 3 (the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface The epoxy resin composite material is formed by compounding the rare earth composite magnetic material in Example 4 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 50wt%) with epoxy resin as a functional filler, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 0.4mm. The fourth-to-last layer structure is an epoxy resin composite material formed by compounding the rare earth composite magnetic material in Example 4 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 50wt%) with epoxy resin as a functional filler, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 0.4mm. The upper structure is an epoxy resin composite material formed by compounding the rare earth composite magnetic material in Example 5 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 60wt%) with epoxy resin as a functional filler, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 0.4mm.

[0102] The relationship between the electromagnetic wave reflection loss and frequency of the rare earth composite magnetic absorbing material obtained by the present invention with different number of layers is shown in the figure Figure 4As shown, compared with the single-layer FeSiAl absorbing material (1 layer) (the single-layer FeSiAl absorbing material is an epoxy resin composite material formed by compounding the rare earth magnetic material in Example 1 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 0wt%) as a functional filler with epoxy resin, the rare earth magnetic material filling amount is 75wt%, and the total thickness of the single-layer FeSiAl absorbing material is 2mm), the absorption bandwidth of the rare earth composite magnetic absorbing material increases first and then decreases with the increase of the number of layers. Under the three-layer structure design, the rare earth composite magnetic absorbing material has broadband absorption characteristics and good absorbing performance. Too few or too many layers are not conducive to the improvement of absorbing performance and absorption bandwidth. In the three-layer structure design of Example 9 Under the rare earth composite magnetic absorbing material, the bandwidth with a reflection loss of no more than -8dB can reach 4.8GHz, which is much higher than the effective bandwidth (0GHz) of the single-layer FeSiAl absorbing material (1layer), the effective absorption bandwidth (2GHz) of the rare earth composite magnetic absorbing material under the 2-layer structure design in Example 8, the effective absorption bandwidth (3.2GHz) of the rare earth composite magnetic absorbing material under the 4-layer structure design in Example 10, and the effective absorption bandwidth (2.3GHz) of the rare earth composite magnetic absorbing material under the 5-layer structure design in Example 11. In addition, under the rare earth composite magnetic absorbing material with a three-layer structure design in Example 9 of the present invention, the minimum reflection loss (-9.8dB) is also better than the rare earth composite magnetic absorbing materials composed of other layer structures. The results show that the multi-layer structure design is conducive to further improving the electromagnetic wave absorption capacity of the absorbing material.

[0103] Example 12

[0104] A rare earth composite magnetic absorbing material with a three-layer structure is provided, wherein the lower layer structure is an epoxy resin composite material formed by compounding the rare earth composite magnetic material in Example 2 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 20wt%) as a functional filler with epoxy resin, the rare earth composite magnetic material filling amount is 75wt%, and the thickness is 0.6mm, and the middle layer structure is an epoxy resin composite material formed by compounding the rare earth composite magnetic material in Example 3 (the doping amount of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid on the surface is 40wt%) as a functional filler with epoxy resin, and the rare earth composite magnetic material filling amount is 75w t%, and a thickness of 0.6mm. The upper structure is an epoxy resin composite material formed by the rare earth composite magnetic material in Example 7 (the surface of the undehydrogenated samarium iron boron rare earth permanent magnet alloy particles modified with oleic acid has a doping amount of 60wt% and has been subjected to gradient annealing treatment) as a functional filler and epoxy resin. The filling amount of the rare earth composite magnetic material is 75wt%, and the thickness is 0.8mm. The reflection loss of the rare earth composite magnetic absorbing material under the three-layer structure design is not more than -8dB. The bandwidth can reach 6.0GHz, and the minimum reflection loss is -10.6dB, which is better than the minimum reflection loss (-9.8dB) of the three-layer rare earth composite magnetic absorbing material without annealing.

[0105] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A rare earth composite magnetic material, characterized in that: The rare earth composite magnetic material comprises composite rare earth permanent magnet alloy particles and magnetic metal powder, and the surface of the rare earth permanent magnet alloy particles is modified with oleic acid.

2. The rare earth composite magnetic material according to claim 1, characterized in that: The rare earth permanent magnet alloy particles are compounded with magnetic metal micropowders through solvent-induced dispersion.

3. The rare earth composite magnetic material according to claim 1, characterized in that: The rare earth permanent magnet alloy particles are MFeB, wherein M is Sm, Ce or Nd; and / or The magnetic metal powder is FeCo and / or FeSiAl. Preferably, the particle size of the magnetic metal powder is 20 to 50 μm.

4. A rare earth composite magnetic absorbing material, characterized in that: The rare earth composite magnetic absorbing material is obtained by arranging the rare earth composite magnetic material according to any one of claims 1 to 3 in multiple layers according to the impedance matching principle; Preferably, before the multi-layer arrangement, the rare earth composite magnetic material is firstly compounded with epoxy resin to form an epoxy resin composite material, and then the epoxy resin composite material is arranged in multiple layers according to the impedance matching principle.

5. The method for preparing the rare earth composite magnetic absorbing material according to claim 4, characterized in that: The method comprises the following steps: (1) preparing rare earth permanent magnet alloy particles with surface modification of oleic acid; (2) compounding the rare earth permanent magnet alloy particles whose surfaces are modified with oleic acid with magnetic metal micropowders to obtain rare earth composite magnetic materials; (3) Arranging the rare earth composite magnetic material in multiple layers according to the impedance matching principle to obtain a rare earth composite magnetic absorbing material.

6. The preparation method according to claim 5, characterized in that: Step (1) includes the following sub-steps: (11) placing the rare earth permanent magnet alloy block, oleic acid, organic solvent, and grinding balls in a ball milling jar and performing ball milling in a planetary ball mill to obtain a ball milled material; (12) using a suction filter funnel to separate the ball mill material into solid and liquid to obtain a precipitate, then adding an organic solvent to wash it, and then filtering to separate the precipitate; (13) The precipitate separated by filtration is placed in an oven for drying to obtain rare earth permanent magnet alloy particles with oleic acid modified on the surface.

7. The preparation method according to claim 6, characterized in that: In step (11), the mass ratio of the rare earth permanent magnet alloy block, oleic acid, organic solvent, and grinding ball is 1:(0.3-1):(0.3-2):(1-4); In step (11), the ball milling speed is 100 to 800 rpm, and the time is 0.5 to 24 hours; In step (11) and / or step (12), the organic solvent is one or more of n-heptane, ethanol, and acetone; and / or In step (13), the drying temperature is 60°C to 150°C, and the drying time is 2 to 24 hours.

8. The preparation method according to claim 5, characterized in that: Step (2) is: The rare earth permanent magnet alloy particles with oleic acid on the surface are dispersed in deionized water and / or an organic solvent, and then magnetic metal micropowder is added and stirred evenly, and then centrifuged, washed and dried in sequence to obtain a rare earth composite magnetic material.

9. The preparation method according to claim 8, characterized in that: In step (2): The organic solvent used for dispersing the rare earth permanent magnet alloy particles whose surfaces are modified with oleic acid is ethanol and / or acetone; The mass ratio of the rare earth permanent magnet alloy particles modified with oleic acid on the surface to the magnetic metal fine powder is (0-0.6):1, preferably (0.2-0.6):1; The stirring speed is 100 to 800 rpm, and the time is 2 to 24 hours; The centrifugal speed is 2000-13000 rpm, and the time is 5-30 min; and / or The drying temperature is 60° C. to 150° C., and the drying time is 2 to 24 hours.

10. The preparation method according to claim 5, characterized in that: In step (3): The rare earth composite magnetic material is arranged in multiple layers by optimizing the matching thickness and concentration between different layers to obtain a rare earth composite magnetic wave absorbing material; Preferably, before the multi-layer arrangement, the rare earth composite magnetic material is firstly compounded with epoxy resin to form an epoxy resin composite material, and then the epoxy resin composite material is arranged in multiple layers by optimizing the matching thickness and concentration between different layers.

Citation Information

Patent Citations

  • Preparation method of anti-corrosion rare earth permanent magnet material

    CN107983960A

  • Manufacturing for rear-earth magnet

    JP1996130142A

  • NdFeB / FeCo NANO COMPOSITE MAGNET

    JP2010074062A

Cited By

  • Ultra-wideband electromagnetic wave absorption metamaterial based on rare earth soft magnetism and design method thereof

    CN121645819A